(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The rising demand for traditional building materials has exposed a notable disparity between their supply and demand. Concurrently, the disposal challenge posed by waste plastics like PET and PP is intensifying, given that only a small fraction of PET bottles are recycled. Additionally, despite the ubiquity of laterite quarry waste, its potential remains largely untapped India, where each person produces an average of 0.5 grams of plastic waste daily, has been delving into the feasibility of creating sustainable bricks from plastic waste, quarry dust, and M sand (manufactured sand). This innovative approach seeks to leverage the durability of plastics in a circular economy, promoting their reuse after their primary lifecycle, thereby ensuring minimal environmental impact while generating financial value. Results from the study indicate that incorporating plastic waste, quarry dust, and M-sand in brick manufacturing enhances the brick’s strength and density while reducing water absorption. Bricks composed of 20% plastic waste, combined with 10% each of quarry dust and M-sand, demonstrated optimal characteristics. These bricks rival traditional red bricks in terms of neat finish, water absorption, and compressive strength. In high altitude regions lacking efficient waste disposal systems, accumulating non-degradable plastic waste becomes not only an eyesore but also an environmental hazard. By converting this waste into high-strength bricks, which offer sound and thermal insulation benefits, we not only curb plastic pollution but also reduce the overall construction costs. This approach also alleviates the need for sand extraction from vital riverbeds. These waste-derived bricks present a promising alternative to conventional building materials. Still, more research is essential to assess the bricks’ long-term resilience under different environmental conditions and to evaluate the feasibility of scaling up their production. In essence, integrating plastic waste in brick manufacturing offers a sustainable solution to meet the construction industry’s demands and manage plastic waste effectively.